Internalisasi Nilai-nilai Spiritual pada Konsumen Produk HNI-HPAI (Studi kasus di Cordova Halal Mart) - Rahimah Andesmi (Jurnal Penelitian Ilmu Ushuluddin, 2022)
Research conducted on HNI-HPAI consumers at Cordova Halal Mart aims to examine the effect of internalizing spiritual values applied by mentors.  The method used is a qualitative descriptive method.  Information on the influence of internalizing spiritual values was obtained from interviews, observations and documentation.  This research shows that the internalization carried out is effective, as evidenced by the inherent values taught to consumers.  There are four important aspects emphasized by the mentor, namely prayer, remembrance, infaq and alms.  In the process of course there are supporting factors including self-awareness, family environment, community environment and the scope of friendship.  While the inhibiting factors include work and the community environment.